If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -5 = (-10) Reorder the terms: -5 + 5x = (-10) -5 + 5x = -10 Solving -5 + 5x = -10 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 5x = -10 + 5 Combine like terms: -5 + 5 = 0 0 + 5x = -10 + 5 5x = -10 + 5 Combine like terms: -10 + 5 = -5 5x = -5 Divide each side by '5'. x = -1 Simplifying x = -1
| 3e=9 | | K-12=3k | | 4x^2+39x+90=0 | | 2(b-4)=-2b+8 | | 2x-32=180 | | 14+5n=4+17 | | -2x+2=-5+16 | | 12y^2=5y+3 | | 1.86g-10=0.23 | | 2x+3x+100=180 | | 5(0.45)=1.70 | | -24*4-53=39-4 | | 4b-3-8b-9= | | f=1.8c+32+16 | | x+59=69 | | 3x-1=40 | | 4x-6+22=7 | | 1=2k | | 5(2x-3)-2(x+1)=x-4 | | 5z-7=23 | | 5z-7= | | ln(x+5)-Ln(x-1)=-ln(x+1) | | 10=3+e | | 2x^2+3x=16x+7 | | -18=x-18 | | -8x+30=10 | | 6-2(3-2x)=-4(3-x) | | -5d=10 | | z-4(z+2)=3(z-4)-2z | | 4(x+2)=14+-2(3+4x) | | -2(6-3x)=-12+6x | | 2m^2+15m+25=0 |